Elitism and the Informal Economy in the Age of Globalization - Okeke, Remi Chukwudi; Anyadike, Omumu Nkechinyere (NIU Journal of Social Sciences; Vol 6 No 3 (2020): KIU Journal of Social Sciences, Vol. 6 No. 3, September 2020, 2020)
This paper discusses elitism and the informal economy in the age of globalization. It probes the divergent meanings of the informal economy and elucidates on the concept of the elitist state. It interrogates globalization. A specific focus was made in the study on the Nigerian state in West Africa. Findings of the study suggest that in this country, the relationship between the informal economy and the state is marred by immense contradictions, bordering principally on elitism (in the age of globalization). The paper postulates that in the age of globalization (and always) socio-economic development remains peripheral when devoid of some backward and forward linkages between the formal and informal economies. The theoretical framework of the contribution is the elite theory. Keywords: Elitism, informal economy, formal economy, elitist state, elite theory, Globalization